The Missing News - Robert A. Hackett, Richard Gruneau, Donald Gutstein, Timothy A. Gibson, and News Watch Canada (University of Toronto Press, 2000)
When at its best, journalism in a liberal democracy holds government and other power-holders accountable by investigating their actions and decisions, thus truly informing people. It fosters participation in public life by providing a forum for civil debate (one definition of democracy is "government by discussion"). It helps clarify policy and value choices, and effectively filters information (using criteria of public relevance, interest and significance) so that citizens are not overwhelmed by infoglut. At the same time, it must fairly reflect the diversity of reasonable voices, viewpoints, and often competing political perspectives in Canadian society. All that is a tall order. Generally speaking, Canada's news media do a reasonable job of living up to these high standards. Still, there are enough examples of media failings to warrant a systematic examination of the Canadian news media. How do newspapers and TV stations decide what news we will receive, whose letters will be published, or who will be accorded credibility? Are all the socially important stories that might be told actually making it into the mainstream? If not, why not? Finding answers to those questions is what NewsWatch Canada is all about. But, before learning about it, we should first learn something about an American research group, "Project Censored." Watergate, the early 1970s U.S. political scandal that led to the unprecedented resignation of a president, has achieved mythical status in American journalistic culture. The exploits of Washington Post reporters Bob Woodward and Carl Bernstein turned on a generation of young journalists to the notion of being investigative reporters. But what is often forgotten is that the Post was almost alone on the story until after Richard Nixon was re-elected president in 1972. Many senior pundits thought Watergate was a non-story. At one point, Katherine Graham, the Post's legendary publisher, asked her equally legendary editor Benjamin Bradlee, "If this is such a hell of a story, where is everybody else?" This question caught the attention of Carl Jensen, a professor of communications at Sonoma State University in California, and prompted him to do some digging of his own. Jensen found that many alternative publications were breaking stories on Watergate that the mainstream media were ignoring. From that, he developed the idea that someone should survey the alternative and mainstream press to see whether other socially important stories were failing to get the attention they deserved.